Differing temperature dependencies of functional homologs zebrafish Abcb4 and human ABCB1 - Luckenbach, Till; Burkhardt-Medicke, Kathleen (Frontiers in Pharmacology, 2024)
The ATP binding cassette (ABC) transporters human ABCB1 and zebrafish (Danio rerio) Abcb4 are functionally homologous multixenobiotic/multidrug (MXR/MDR) efflux transporters that confer the efflux of a broad range of diverse chemical compounds from the cell. As ATPases, the transporters utilize the energy released by ATP cleavage for protein conformation changes and concomitant active transport of substrate compounds. The temperatures, at which human ABCB1 and zebrafish Abcb4 need to function, can substantially differ: Whereas the ambient temperature of human ABCB1, which is that of the human body, is constant, zebrafish Abcb4 has to be active in a wider temperature range as the body temperature of zebrafish can considerably vary, depending on the ambient water temperature (18°C to 40°C). Here, we examined the effect of temperature on the ATPase activities of recombinant human ABCB1 and zebrafish Abcb4 generated with the baculovirus expression system. Incubation temperatures for enzyme reactions were set to 37°C and 27°C, corresponding to the human body temperature and the cultivation temperature of zebrafish in our lab, respectively. For stimulation and inhibition of zebrafish Abcb4 and human ABCB1 ATPase activities verapamil and cyclosporin A were added at different concentrations and 50% effect concentrations (EC50) were determined. The different temperatures had a stronger effect on the human ABCB1 than on the zebrafish Abcb4 ATPase: Differences between EC50 values for verapamil at 37°C and 27°C, respectively, were 1.8-fold for human ABCB1 but only 1.2-fold for zebrafish Abcb4. Activation energies (Ea) of basal and verapamil-stimulated ATPases, calculated based on the Arrhenius equation, were 2-fold (basal) and 1.5-fold (verapamil-stimulated) higher for human ABCB1 than for zebrafish Abcb4. The differences between zebrafish Abcb4 and human ABCB1 ATPases in temperature sensitivity and activation energy could be important for the comparison of the functional properties of the two transporter proteins in the context of pharmaco-/toxicokinetics. Related to this, our finding that at equal reaction conditions the zebrafish Abcb4 ATPase activity tended to be generally higher that of human ABCB1 may also be important, as this may point to a higher substrate compound transport rate of Abcb4.